2006
DOI: 10.1017/s0140525x06009332
|View full text |Cite
|
Sign up to set email alerts
|

Why ritualized behavior? Precaution Systems and action parsing in developmental, pathological and cultural rituals

Abstract: Ritualized behavior, intuitively recognizable by its stereotypy, rigidity, repetition, and apparent lack of rational motivation, is found in a variety of life conditions, customs, and everyday practices: in cultural rituals, whether religious or non-religious; in many children's complicated routines; in the pathology of obsessive-compulsive disorders (OCD); in normal adults around certain stages of the life-cycle, birthing in particular. Combining evidence from evolutionary anthropology, neuropsychology and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
349
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(375 citation statements)
references
References 379 publications
(348 reference statements)
16
349
1
9
Order By: Relevance
“…The results showed that checking symptoms are specifically related to the tendency to identify routine actions in terms of concrete mechanistic details. These results are consistent with the recent theoretical suggestion that ritualized action is not connected to a representation of a goal, which is not in fact accessible (Boyer & Liénard, 2006). In the absence of goal representations, gestural representations guide actions (Wegner et al, 1984), which may lead checking-prone individuals to be 'task-oriented' (i.e., focused on performance), rather than 'goal oriented' (i.e., focused on implications).…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that checking symptoms are specifically related to the tendency to identify routine actions in terms of concrete mechanistic details. These results are consistent with the recent theoretical suggestion that ritualized action is not connected to a representation of a goal, which is not in fact accessible (Boyer & Liénard, 2006). In the absence of goal representations, gestural representations guide actions (Wegner et al, 1984), which may lead checking-prone individuals to be 'task-oriented' (i.e., focused on performance), rather than 'goal oriented' (i.e., focused on implications).…”
Section: Discussionsupporting
confidence: 90%
“…Consistently with this idea, checking individuals seem to parse their habitual actions mainly with regard to movement parameters, rather than goals and outcomes (Belayachi & Van der Linden, 2009). However, anxiety, which focuses attention on details and promotes local perceptual information processing, could alter the shift of attention towards effect representation (Boyer & Liénard, 2006;Derryberry & Reed, 1998). Thus, as we did not control for the impact of anxiety, attention and dissociation in this study, we cannot rule out the possibility that those factors may account, at least in part, for the relationship found between checking symptoms and low sense of agency.…”
Section: Discussionmentioning
confidence: 89%
“…One way of answering this question would be to explore the extent to which priming the concept of success may increase feelings of self-causation in checking individuals, and the extent to which inducing checking may engender an undermined experienced agency and less confidence in self-agency. Nevertheless, we assumed that an impaired feeling of doing may constitute only one of the numerous factors implicated in checking, such as anxiety, attentional focus, reality monitoring difficulties and poor memory for actions (Boyer & Liénard, 2006;Zermatten & Van der Linden, 2008b). As mentioned above, anxiety and attentional focus may have a potential confounding effect as those variables may interfere with the normal processing of action-monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emotion regulation need not be the only mechanism in rituals to prevent practitioners from forming strong individual memories. Demanding behavioural procedures and exhausting verbal performances are commonly employed in rituals (Bloch, 1986;Rappaport, 1999;Liénard and Boyer, 2006;Boyer and Liénard, 2007). Such behaviours may have similar depleting efffects on the executive system and thus function to impair individual memory and facilitate a collective mnemonic reconstruction of the event (Schjoedt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%